Manfaat Bahasa Daerah Banten di Sekolah Dasar (Sunda dan Jaseng) - Ratna Dewi; Nadiva Dewi Maulina; Devi Nurviyanti; Santia Nengsih (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
Regional languages play a crucial role in shaping cultural identity and strengthening local values among young generations. This study aims to examine the benefits of using regional languages of Banten, specifically Sundanese and Javanese Serang (Jaseng), in learning activities at elementary schools. The method used is descriptive qualitative with data collection techniques through observation, interviews with teachers, and documentation studies at several elementary schools in Banten. The results show that the use of regional languages can increase students' self-confidence, strengthen their ties to local culture, and promote the preservation of regional languages in the midst of globalization. Additionally, students become more active in communication and demonstrate intercultural tolerance attitudes. The conclusion of this study is that regional languages not only function as a means of communication but also as an educational tool in shaping character and love for one's own culture.